Bridging Standards and Identity: Integrating National and International Accreditation to Strengthen the Quality and Global Competitiveness of Indonesian Higher Education - Yulia Luthfiyani Azizah; Subiyantoro (Managere: Indonesian Journal of Educational Management, 2025)
This study aims to analyze the urgency of national and international accreditation for universities in Indonesia in facing the dynamics of globalization of higher education. Using a library-based qualitative research approach, this study examines various documents, regulations, and academic literature from accreditation institutions such as BAN-PT, AUN-QA, ABET, AACSB, and ISO 21001. The analysis was carried out through content analysis techniques with the stages of unitizing, coding, categorization, and synthesis to identify conceptual patterns between national and international accreditation systems. The results of the study show that national accreditation serves as an external legal and quality assurance mechanism that ensures the conformity of universities with national standards, while international accreditation strengthens global reputation and expands cross-border academic networks. The integration of the two accreditation systems results in an adaptive quality assurance model that balances regulatory compliance and continuous improvement. In practical terms, the results of the research provide a strategic basis for the development of a sustainable higher education accreditation and internationalization policy that is sustainable, competitive, and relevant to the local context.